Coesão referencial por substituição lexical sinonímica na produção escrita de fanfictions : uma proposta intervencionista de ensino - Santos, Erisvaldo Silva (2020)
When writing is understood as a process-based collaborative social practice and taught through several literacy models, it incentivizes student protagonism and hence their active participation in society. For this reason, writing, done in a meaningful and contextualized learning perspective, is considered not only a process that develops the senses, linguistic abilities and capabilities, but also as one that encompasses the planning-production-revision triad. The present research/action work aims at introducing improvements on the 9th graders’ text production at Colégio Estadual Almirante Barroso. That is a school located in the city of Muribeca, state of Sergipe, Brazil. To accomplish our task, it has been paramount to address the following query: what teaching strategies can help students reduce their repetitive use of lexical items and improve cohesiveness in their writing? Within this context, we have identified and analyzed the learners’ weaknesses concerning the substitution of lexical synonyms; presented a proposal of intervention to contribute to the development of text cohesion ability; and fostered digital literacy by making use of multimedia resources for online collaborative writing, thus providing efficiency to the writing ability as a tool for youth protagonism and social inclusion. In order to do so, we have considered the text as a place for interaction between subjects and for an interactional buildup of the senses which, in other words, is a sociocognitiveinteractionist perspective. It is noteworthy that such study is based on the theoretical premises of official referential documents for the education in Brazil, i.e. PCN (1997) and BNCC (2018); Textual Linguistics, concerning referential cohesion, textuality and text production, by Koch (1999; 2009; 2015), Koch and Elias (2011; 2015; 2017), Fávero (2002) and Marcuschi (2004; 2008; 2012); Projção Social da Escrita, by Coulmas (2014), which highlights the role and the contributions of writing to society; Social Literacies by Street (2019), which defines literacy as a social practice and depicts policies that address reading and writing; Lexicologia, with Antunes (2005; 2009; 2012), which validates lexicon’s cohesive function in building a text and basic notions on textual property of cohesion and coherence; Letramentos Múltiplos, with Rojo (2012; 2013), which discusses the need for schools to find their place in the cyberspace and to promote multiliteracies in multisemiotic genres; and the study the fanfiction genre, by Vargas (2015), which highlights the spontaneous transposition of traditional means of text creation and reception into new technologies, and the youth autonomy for selecting and publishing fictional texts of their own interest through electronic media. As a teaching interventionist and pedagogical product, we have produced a Pedagogical Notebook based on the work done on the fanfiction genre and on the presentation of a Didactic Sequence (DS). Such Didactic Sequence has been adapted from Dolz, Noveraz and Schneuwly’s (2004) proposition, and encompasses reading, text comprehension and production. In addition, this DS also activates students’ word choices and vocabulary expansion. The results not only point to an expressive upgrade in the students’ vocabulary range and in their adequate use of synonyms when writing fanfictions, but also raise awareness to multiple literacies and semiosis. This work is therefore highly relevant due to its contribution for the advancements in written text research, especially in basic education. Furthermore, it serves as subsidies for the pedagogical practice of Portuguese teachers.